Continuous Fixed-Bed Column Study and Adsorption Modeling: Removal of Lead Ion from Aqueous Solution by Charcoal Originated from Chemical Carbonization of Rubber Wood Sawdust - Swarup Biswas; Umesh Mishra (Journal of Chemistry)
The efficiency of chemically carbonized rubber wood sawdust for the removal of lead ion from the aqueous stream was investigated by column process. Chemically carbonized rubber wood sawdust was prepared by treating the sawdust with H2SO4 and HNO3. Maximum removal of lead ion in column process was found as 38.56 mg/g. The effects of operating parameters such as flow rate, bed depth, concentration, and pH were studied in column mode. Experimental data confirmed that the adsorption capacity increased with the increasing inlet concentration and bed depth and decreased with increasing flow rate. Thomas, Yoon-Nelson, and Adams-Bohart models were used to analyze the column experimental data and the relationship between operating parameters. Chemically carbonized rubber wood sawdust was characterized by using Fourier transform infrared spectroscopy. Scanning electron microscope was also utilized for morphological analysis of the adsorbent. Furthermore X-ray fluorescence spectrum analysis and energy dispersive X-ray spectroscopy were also used for the confirmation of lead adsorption process.